POTENSI TONGKOL JAGUNG (Zea Mays L.) SEBAGAI SUNSCREEN DALAM SEDIAAN HAND BODY LOTION - Dewi Ekowati; Inaratul Rhizky Hanifah (Jurnal Ilmiah Manuntung, 2016)
The over exposure sunlightis on the skin provides of damage. Skin damage caused the over exposure sunlightis can occur in the short term such as erythema or long term such as premature skin aging and even skin cancer. One way that can be done to minimize the amount of UV that penetrated into the skin is to use sunscreen. Corn cob contain the chemical compounds of phenolic, which suspected to have the protection activity toward the UV B rays. The study aims to make preparations hand body lotion that meet good physical quality of the corn cob extract  as a sunscreen. Hand made three body lotion formula with extract concentrations of corn cob 10% FI, FII FIII 15% and 20%. Testing the physical properties of the test hand body lotion include viscosity, dispersive power and pH. The effectiveness of a sunscreen is based on a determination of the value of the Sun Protection Factor (SPF) in vitro. The third formula has a good physical quality lotion that viscosity 50-1000 dPas, the scatter 5-7 cm, pH 4.5 -7. The effectiveness of sunscreen based on the value of the Sun Protection Factor (SPF), the effectiveness FIII in the category of extra protection is 7.23. SPF value FI  FII 5.13 and 5.67 so that FI and FII into the category of moderate protection